G336(P) The impact of a youth violence intervention programme on reattendance rates and young people's wellbeing. (12th March 2018) - Travers, C; Hann, G
Abstract : Introduction: Tackling gang violence is a significant challenge. With knife crime and serious youth violence on the rise, the Government has looked towards alternatives to punitive measures. Hospital-based youth violence intervention programmes (YVIP) are one alternative that aim to reduce risk and increase protective factors for gang-related youth violence. Users views of YVIPs have yet to be evaluated in the UK. Aims: We had 2 main aims: to compared reattendance rates to A&E of those who engaged with the YVIP and those that refused engagement to evaluate the YVIP by examining exit surveys of the young people who had completed the programme Methods: The reattendance rates were analysed for those attending for gang violence who either fully engaged, partially engaged or refused to engage with the programme. The exit survey responses of those patients who had fully engaged were evaluated. The exit survey contained statements that the completed service users responded to based on how strongly they agreed/disagreed with statements. This allowed self-assessment about whether the YVIP had any impact on their lifestyle. Results: Since its inception in October 2014, the YVIP had received 465 referrals. Only 18% (85 patients) engaged with the service. At the time of study only 15 services users fully engaged and completed the programme. Those patients who had fully engaged had lower reattendance rates (6.7%) than those patients who engaged and dropped out (19%) or those who had refused to engage (26.7%). Every completed service user felt that the YVIP had provided helpful support. 33.3% (5/15) strongly agreed that they were much happier since joining the programme. 33.3% (5/15) agreed that they were happier and 33.3% (5/15) were neutral. 73.3% (5/15) felt they were less likely to reattend A and E due to youth violence, whilst 26.7% (4/15) were neutral. 100% (15/15) strongly agreed that it is a good idea to have a youth support service in the hospital. Conclusions: Although it is hard to engage young people who have been involved in gang violence, there is evidence of the usefulness of YVIPs on both reattendance rates and the well being of those who engage.